Hair Loss Associated with Sertraline: A Case Report - Seyed Hamzeh Hosseini; Hamed Ghazvini; Seyedeh Masoumeh Seyedhosseini Tamijani; Raheleh Rafaiee (Case Reports in Clinical Practice)
Sertraline is classified as a selective serotonin reuptake inhibitor (SSRI) that is extensively employed in the management of a range of psychiatric conditions, encompassing major depressive disorder and anxiety disorders. While the overall incidence of hair loss is not extensively documented, it is recognized as a possible cutaneous reaction to SSRIs, including sertraline. In the present study, we report the case of a 16-year-old Iranian female of Persian ethnicity who had been treated for panic disorder. She developed severe hair loss two weeks post-initiation of treatment with sertraline 50 mg per day. She stopped the medication after two months when she had lost 50% of her hair. The exact mechanism remains unclear, but it is suggested that SSRIs like sertraline may induce hair loss by pushing hair follicles into the telogen phase prematurely, leading to diffuse hair shedding. Management typically involves dose adjustment or discontinuation of sertraline, which has been shown to resolve hair loss in multiple cases. Understanding this phenomenon is crucial for both patients and healthcare providers. Although rare, this side effect can considerably affect a patient’s overall quality of life and compliance with therapeutic regimens.